EPISTEMOLOGI ILMU KEISLAMAN - Huda, Mahmud (Institut Agama Islam Riyadlatul Mujahidin (IAIRM) Ngabar Ponorogo, Indonesia, 2018)
Feelings of curiosity cause humans to always think. There are three objects of human thinking, namely what we want to know (ontology), how knowledge can be (epistemology), and what knowledge is used (axiology). This study discusses the epistemology of Islamic science which aims to: 1) describing the differences between Islamic epistemology and Western epistemology, 2) knowing the method of Islamic epistemology thinking. Through a literature study, findings are made: 1) Western epistemology considers that the object of science is anything that can be sensually observed. So that the source of knowledge according to Western epistemology, namely; empirical, ratio, phenomenon, intuition, and critical thinking. Islamic epistemology recognizes both sensory and metaphysical objects and acknowledges the source of knowledge namely; senses, reason, intuition and revelation. 2) Islamic epistemological thinking methods, namely; Bayani (method of thinking in the ahkami paradigm contained in the science of interpretation, hadith, fiqh, and kalam science), burhani (a method in Islamic philosophy that addresses the philosophical paradigm), irfani (a method of thinking that discusses the paradigm of wijdani in Sufism).